O réquiem divino: a morte de Deus em A gaia ciência de Nietzsche - Souza, Mauro Lúcio Ribeiro de (2007)
The Divine Requiem: God s death in Nietzsche s The Gay Science , aims at describing the path the philosopher took to certify and proclaim the greater of all events. It is in Section 125 of The Gay Science that a madman shouts in the market place that the nihilist society killed God . By replacing the divine figure by the human being, by annihilating the transcendence and affirming the immanence, he promotes the Requiem . The metaphors announced pointed out to the end of a world view that served as the basis for the Western world and had now come to an end. In Nietzsche s opinion, God s death represents the end of the supreme values, the end of the Jewish-Christian moral and the destruction of the Socratic-Platonic metaphysics. A caustic critic of moral and religion, Nietzsche found the key to the labyrinths, showing that both are detractors and deniers of life. For the German philosopher, it was Socrates and his disciple Plato who erected the metaphysics with the dichotomy between the real world and the fake world. However, Nietzsche tries to destroy with his hammering philosophy such paradigm, which obscured the Western world perception for millenniums. The Christian religion is also seen, in his sharp point of view, as a product of the Socratic-Platonic metaphysics, which exhorts the crowd s moral and resentment, therefore denying life as it is here and now, with its happiness and challenges, leading mankind to an after-world existence, a supra-sensitive world. The Christianism is the moral of decadency, according to Nietzsche. His hammer should destroy this world view and create another way to face existence. If God dies, the human being is left with the possibility to construct him/herself, to be sure of life, to accept it